Pengaruh Profitabilitas, Kebijakan Hutang, Ukuran Perusahaan, Pertumbuhan Penjualan Terhadap Praktik Penghindaran Pajak - Winda, Augustpaosa Nariman (Jurnal Paradigma Akuntansi, 2021)
This study aims to study the effect of profitability, debt policy, company size and sales growth on tax avoidance practices on manufacturing companies listed on the IDX in 2017 - 2019. This study uses data from 50 manufacturing companies involved on the IDX in 2017-2019. The regression used to test the research hypothesis is panel data regression. Therefore, before testing hypotheses, classical assumptions are tested. The results showed that profits and total positive assets were significant to the practice of tax avoidance. While debt policy and sales growth have a significant negative effect on tax avoidance practice.